The Influence Of Language Interest On Students Foreign Language Learning Outcomes (Arabic-English) - Irsal Amin (Institut Agama Islam Negeri Padangsidimpuan, 2019)
The problem of learning foreign languages has always been a barrier in the process of learning interaction that makes foreign languages a scourge for students. This also creates certain difficulties for teachers in carrying out the process of teaching foreign languages, not to mention talking about the egoism of teachers who fail to see and develop students' language interests. Previous research studies indicate that the problem of learning foreign languages is a psychological problem.This research is a mixed-method study that combines quantitative-qualitative approaches to explain the influence of language interest on students’ learning outcomes at Al-Abroor Modern Islamic Boarding School in South Tapanuli Regency. The data collection methods in this study used interview and questionnaires to determine language interest and students’ learning outcomes by carrying out written test.The sample in this study were 141 students from a population of 380 people. The data analysis technique in this study used descriptive statistics to find out students' language interest and learning outcomes both in Arabic and English. The findings of this study indicate that students’ language interest is greater in Arabicwith thelanguage interest percentage at 80.60% and learning outcomes at 63.54%. Meanwhile, the English language interest is at 71.48% with learning outcomes at 28.36%. This finding, thus, shows that the difference in students' language interest in Arabic and English is 9.12% with a difference in learning outcomes of 34.87. This research also shows that language interest grows naturally and internally within students which is then strengthened by other supporting factors. In this case, the Arabic language interest in students grew stronger because of the use of Arabic in other subjects. Therefore, it can be concluded that developing language interest can be a factor that supports the successful implementation of language learning.